(untitled) (Unilorin Journal of Lifelong Education, 2025)
The study examined the relationship between conflict management mechanisms and community development among members in Liberty Estate in Ogijo, Ogun State. The study adopted the descriptive survey design. The sample size of 139 participants was selected using the Krejcie and Morgan (1970) formula at 95% confidence level.. Simple random sampling technique was used to select the participants. The self-developed questionnaire was validated for face and content validity and the Cronbach’s alpha co-efficient r-value of =0.81 indicated internal consistency and high reliability. The study’s findings revealed that participants identified ten conflict management mechanisms and considered indigenous participatory approach as the most common mechanism for conflict management in the community. The study found that there was a relationship between conflict management mechanisms and community development among members. The study recommended that community development associations should embrace indigenous participatory approach mechanism for conflict management in communities in Nigeria because members can identify its local mode of operations and it is a cost-effective means of resolving conflicts toward promoting community development among members in communities. Leaders, members, and stakeholders in the community should be trained in the use of indigenous participatory approach and other proactive non-toxic conflict management mechanisms such as collaboration, storytelling, peace counseling, and alternative dispute resolutions for community development